Arkivet som mødested: Odin Teatrets arkiv som teaterhistoriografisk model - Kuhlmann, Annelis (Peripeti, 2010)
Annelis Kuhlmann discusses the newly established archive of Odin Teatret. She finds, however, that the archive of Odin Teatret includes Odin Teatret’s well-known practice of re-circulating artistic material from one performance to another. In this practice one might find a truly new understanding of historiography as directed not only towards preservation, but also towards re-activating preserved historical material, for example through the living theatre’s transmission of archival knowledge.